Immigrant selection and Section 15 of the "Charter": A study of the equality rights of applicants for admission to Canada. - Tie-Ten-Quee, Chantal. (University of Ottawa (Canada), 1995)
This paper argues that non-white applicants for immigration to Canada are a historically disadvantaged group entitled to protection under Section 15 of The Canadian Charter of Rights and Freedoms. It is argued that this group has been discriminated against on the basis of colour, race, ethnic and national origin, in that they were historically denied the advantages of admission to Canada. The current immigrant profile reveals that these historically disadvantaged groups now make up the majority of new immigrants to Canada. This paper argues, however, that when these new immigrants have sought to use equality legislation to challenge immigration selection decisions, that the legislation and the Courts have perpetuated the historic discrimination against them by declining jurisdiction, thereby denying new immigrants the protections of equality legislation. It is proposed that a proper application of basic human rights and Charter principles should provide equality rights and Section 15 protection to applicants for immigration. In order to support this argument the paper takes a historic look at Canadian immigration policy and practice, to illustrate that non-white immigrants to Canada are a historically disadvantaged and powerless group. (Abstract shortened by UMI.)
Keywords: Canadian Studies.